Mental health, well-being and social inclusion in adult street dwellers - Contreras Alfonso, Anny José (2021)
The present analysis, part of an investigation about issues related to adult street dwellers, therefore these issues are: mental health, social inclusion and social well-being in the population named above, therefore it is evident that there is very little research Regarding these issues in the population to work, there are also decrees and laws, which protect the homeless but are not carried out with the population, which shows that a lot of information and research is needed in this regard. The influence that social inclusion has on mental health and social well-being in adult street dwellers is analyzed, through documentary review and in this way, comprehensive care at the psychosocial level is reached, given the foregoing it is evidenced that the relevance of social inclusion in mental health and social well-being in the street dweller is not very important since no aspect regarding the aforementioned issues is worked with the population, which shows that this population is highly vulnerable and not he has a mental health and entities that look after his benefit in every way.